USING OF SOME ENVIRONMENTAL MATERIALS TO OBTAINE SUITABLE MEDIA FOR POTTED PLANTS AND EVALUATION OF FOUR KINDS OF FOLIAR FERTILIZERS THROUGH ITS EFFECT ON (1-VEGETATIVE AND ROOTS GROWTH) OF Nephrolepis exaltata L. - Yousif H. Hammo (Mesopotamia Journal of Agriculture)
This study was conducted in Agricultural College/ Dohuk University during the period between 1st Dec and 1st Dec 2007. The objective was to obtains mixture from available environmental material suitable for potted plants such as Nephrolepis exaltata L. seven mixture of media were used, first (river soil) second (river soil : manure), third (river soil: sawdust), forth (river soil: manure :sawdust), fifth (river soil: manure: sawdust: leave mold), sixth (manure :sawdust), seventh (manure :sawdust: leave mold) (all percentage by volume 1:1) and the interactions with four foliar fertilizer (calcium nitrate , soluble combination fertilizer, Micronate , France) Results showed significant superiority for sixth and seven mixtures in vegetative leave area, leave number fresh weight, root fresh weight by 386.99, 193.65, 246.69, 210.19% consecutively comparing with those grown in first mixture. Also the foliar fertilizer calcium nitrate, soluble combination fertilizer, and France fertilizer significant superiority comparing with Micronate. The interactions between the two factors have significantly effect for all vegetative and characters